Respostas e adaptações de plantas jovens de coqueiro-anão-verde à salinidade do solo e encharcamento - Medeiros, Wiliana Júlia Ferreira de (2016)
The coconut crop in Brazil stands out for its economic and social importance. The coconut cultivation has been in troduced in several regions of the country, however, the Northeast stands out with the largest plantations and production. Currently, a major problem in the agricultural sector, especially in semi-arid regions, has been the process of soil salinization. This problem is accentuated by the use of water with high salt concentration. Another factor existing in saline environments is excess water, especially, in clay soils and with poor drainage. The use of species toler ant to salinity has been a recommended strategy, to promote the rehabilitati on of degraded soils by excess salts. Thus, the objective of this work, was to evaluate the effects of the associations between soil salinity and waterlogging, at the responses and adaptations of young plants of coconut. The work was conducted, in agreenhouse, in the experimental area of the Meteorological Station, Campus Pici, the Federal University of Ceará, in Fortaleza–Ceará, a randomized block design arranged in split plot scheme, with five repetitions, was used.The variables on which the data were collected over time, the experimental design was arranged in split split plots. The plots were formed by five cycles of waterlogging (0; 1; 2; 3 e 4), to 30, 60, 90 e 120 days, lasting four days each cycle, and the subplots were constituted by the five levels of soil salinity (1.70; 11.07; 16.44; 22.14 e 25.20 dS/m). Biometric, physiological a nd nutritional variables were eva luated in plants. In the soil, were evaluated fertility and the electrical conductivity (EC). The growth inhibition of the seedlings was caused more by soil salinity, than by waterlogging. The effects of waterlogging on the growth of plants decreases, with increasing salinity. Gas exchanges were influenced, mainly, by the soil salinity factor, and these responses were related to stomatal causes and not stomatal. The salinity factor resulted in accumulation of P and K in the soil, consequence of lower growth and lower extraction by plants. The reduction in growth and leaf gas exchange is associated with o smotic effects, and an increase in foliar levels of potentially toxic ions (Na+and Cl-). The results did not evidenced nutritional deficiency induction. The coconut plants presented potential to be utilized in revegetation programs, in areas affected by salts, up to the salt level of 11.07 dS/m.